2015
DOI: 10.1111/jvp.12282
|View full text |Cite
|
Sign up to set email alerts
|

Plasma concentrations and sedative effects of a dexmedetomidine, midazolam, and butorphanol combination after transnasal administration in healthy rabbits

Abstract: Plasma concentrations of dexmedetomidine (D = 0.1 mg/kg), midazolam (M = 2 mg/kg), and butorphanol (B = 0.4 mg/kg) were analyzed by liquid chromatography-mass spectrometry (LC-MS/MS) after their simultaneous (DMB) transnasal (TN) administration to healthy rabbits. Time-dependent changes in sedation and antinociception were evaluated by measuring a sedation score based on rabbit's posture, loss of the righting, palpebral and pedal withdrawal reflexes and by instrumental monitoring of rectal temperature, heart r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…In the present study, this association produced high-quality immobilization with rapid and smooth induction. Anaesthesiologic protocols including the association of alpha-2 adrenergic agonists, opioids and benzodiazepines have already been described in veterinary medicine in several species [28,29] Tuval and colleagues (2018), the dosages and total volumes of drugs used in this study were considerably lower, probably also due to the different route of administration. In our study, IM administration was performed in the thigh muscles; no behaviour referable to muscle soreness or pain was observed following injection or during recovery phase, and no bats had difficulty in flying following the procedure.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In the present study, this association produced high-quality immobilization with rapid and smooth induction. Anaesthesiologic protocols including the association of alpha-2 adrenergic agonists, opioids and benzodiazepines have already been described in veterinary medicine in several species [28,29] Tuval and colleagues (2018), the dosages and total volumes of drugs used in this study were considerably lower, probably also due to the different route of administration. In our study, IM administration was performed in the thigh muscles; no behaviour referable to muscle soreness or pain was observed following injection or during recovery phase, and no bats had difficulty in flying following the procedure.…”
Section: Discussionmentioning
confidence: 68%
“…In the present study, this association produced high-quality immobilization with rapid and smooth induction. Anaesthesiologic protocols including the association of alpha-2 adrenergic agonists, opioids and benzodiazepines have already been described in veterinary medicine in several species [28,29]. As regards bats, only Tuval and colleagues (2018) have compared different subcutaneous combinations of medetomidine, MDZ and opioids in R. aegyptiacus with no apparent morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, butorphanol produced higher analgesic efficacy in men in the cold-water stimulus pain model [ 18 ]. Importantly, clearance of butorphanol has been shown to be lower in women compared to men, raising the possibility that pharmacokinetic differences may play a role [ 34 , 35 ]. Finally, studies on gender difference with the use of nalbuphine have been previously scanty and were done with single doses in somatic pain models [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The anesthetic duration of 90 min seems to be a long time period for injectable anesthesia compared to our data. Santangelo et al reported that the transnasally administered anesthetic mixture of dexmedetomidine (DXM): 0.1 mg + MID: 2 mg + BUT: 0.4 mg/kg caused deep sedation and analgesia suitable for minor surgical procedures in rabbits [24]. DXM is an alpha 2 -adrenergic receptor agonist and has a double potency of an equal dose of MED [5].…”
Section: Discussionmentioning
confidence: 99%